Le bâtiment routier du col de Montgenèvre (Hautes-Alpes) : fouille archéologique et patrimonialisation d’une traversée alpine - Philippe Leveau; Patrick Reynaud (Gallia)
In 2010, a preventive archaeology operation uncovered the southwest corner of a building from the Roman era that was set around a courtyard portico. Its layout, which approximates that of the hostels to be found in the Little and Great St Bernard passes, and its proximity to a Roman road and to a monumental shrine, suggest that it was used to accommodate those travelling through the pass. This publication provides an opportunity to take stock of the archaeological discoveries made in the pass. Extending to an exploration of the question of road traffic in the province of the Cottian Alps, the article highlights the effects of the heritage process that makes this pass the starting point for the Via Domitia, and proposes a re-interpretation.